A Public Health Policy Perspective on the Effective Implementation of Digital Therapeutics in India - Banerjee, Saurabh Kumar; Choudhary, Nikita (National Journal of Community Medicine, 2025)
Digital Therapeutics (DTx) represent a novel category of medical interventions that utilize software applications to prevent, manage, or treat various health conditions. Global evidence from nations like Germany, the United States, and Japan have demonstrated the effectiveness of digital therapeutics (DTx) in the healthcare systems. India needs to implement a comprehensive policy strategy to integrate the (DTx) in the public health ecosystem. Initially, the Central Drugs Standard Control Organisation (CDSCO) ought to officially acknowledge Digital Therapeutics (DTx) as a separate category within Software as a Medical Device (SaMD). Next, the National Health Authority (NHA) should test reimbursement models under the Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (PM-JAY). Additionally, it is essential for DTx platforms to comply with the interoperability standards established by the Ayushman Bharat Digital Mission (ABDM). Furthermore, the challenge of human resources needs to be considered within the policy structure. Lastly, attention should be given to the pace and evolution of development to incorporate Public Private Partnerships (PPPs). Thus, it can be concluded that the process of integrating digital therapeutics (DTx) into the public health systems has the potential to improve operational efficiency, stimulate better engagement on the side of patients, and lower the long-term cost of healthcare delivery.